Lenvatinib as second-line treatment in patients with unresectable hepatocellular carcinoma: A retrospective analysis - Qin, He-nan; Ning, Zhen; Sun, Rui; Jin, Chen-xing; Guo, Xin; Wang, A-man; Liu, Ji-wei (Frontiers in Oncology, 2022)
Objective: The purpose of this study is to determine the efficacy and safety of lenvatinib as second-line setting in Chinese patients with unresectable hepatocellular carcinoma (HCC). Methods: We performed a retrospective analysis of Chinese patients with unresectable HCC who received second-line treatment of lenvatinib at three institutions from November 2018 to February 2022. Demographic and clinicopathologic characteristics, data on the treatment regimens were obtained from medical records. Clinical response was evaluated every 4–6 weeks following treatment beginning based on modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria. Results: In total, 50 patients with unresectable HCC who received second-line treatment of lenvatinib were enrolled in this study. The objective response rate (ORR) was 18.0% and disease control rate (DCR) was 74.0%, respectively. The duration of response (DoR) was 6.0 months. The median progression-free survival (PFS) and overall survival (OS) were 5.0 and 8.5 months, respectively. Patients who received ICIs combined with anti-angiogenic inhibitors as first-line therapy, achieving CR/PR at first-line therapy, with PFS≥6months at first-line therapy had a higher DCR. Univariate and multivariate analysis showed that AFP (ng/ml)<400, absence of extrahepatic metastasis, Child-Pugh A, tumor number<3, ICIs combined with anti-angiogenic inhibitors as first-line therapy, CR/PR to first-line therapy and PFS≥6months at first-line therapy were independent factors of favorable PFS. Univariate analysis showed that absence of extrahepatic metastasis, tumor number<3, ICIs combined with anti-angiogenic inhibitors as first-line therapy and PFS≥6months at first-line therapy were significantly associated with longer OS. Multivariate analysis showed that absence of extrahepatic metastasis, Child-Pugh A, tumor number<3, CR/PR to first-line therapy and PFS≥6months at first-line therapy were independent prognostic factors of OS. The majority of AEs were grade 1-2, and were reversible. Grade 3/4 AEs occurred in 12 patients (24.0%) and were mostly connected with hand-foot skin reactions (10.0%), and 10 patients had lenvatinib dose reductions. Two toxicity-related treatment interruptions were attributed to grade 3 hand-foot skin reaction, and grade 4 proteinuria, respectively. Conclusion: This study confirms the efficacy and safety of lenvatinib as second-line therapy after progression on sorafenib or ICIs combined with anti-angiogenic inhibitors.